Clinical Analysis of Cervical Lymph Node Metastasis Risk Factors and the Feasibility of Prophylactic Central Lymph Node Dissection in Papillary Thyroid Carcinoma. (31st January 2021) - Chen, Yifan; Chen, Shuo; Lin, Xiaoying; Huang, Xiangqing; Yu, Xiaofang; Chen, Juying
Abstract : Objective . To identify the risk factors for cervical lymph node metastasis (CLNM) and the feasibility of prophylactic central lymph node dissection. Methods . The characteristics of 1107 patients were extracted and analyzed. Univariate and multivariate analyses were used to identify risk factors associated with lymph node metastasis. The relationship between the central lymph node dissection (CLND) and lateral lymph node metastasis (LLNM) was analyzed using the correlation analysis. Results . The probability of CLNM was closely related to the male gender, age <55, and the increase of tumor size. Those patients with an increase in tumor size and CLNM were extremely prone to LLNM. Also, LLNM was more likely to happen in those with the more positive central lymph nodes. Routine prophylactic central lymph node dissection (P-CLND) did not increase the risk of complications. Conclusion . P-CLND should be considered as a reasonable surgical treatment for PTC.